Control the deposition uniformity using ring cathode by DC discharge technique - Aadim, Kadhim A. (Iraqi Journal of Physics, 2019)
Simulation of direct current (DC) discharge plasma usingCOMSOL Multiphysics software were used to study the uniformityof deposition on anode from DC discharge sputtering using ring anddisc cathodes, then applied it experimentally to make comparisonbetween film thickness distribution with simulation results. Bothsimulation and experimental results shows that the deposition usingcopper ring cathode is more uniformity than disc cathode